The Roles of Productive Safety Net Program (PSNP) On the Practices of Soil and Water Conservation in the Case of Sekela District, Amhara State, Ethiopia - Tilahun, Abineh; Teferie, Bogale (International Journal of Geography and Geology, 2015)
The introduced Soil and Water Conservation (SWC) techniques, practices in the study area were started through the Productive Safety Net Programme (PSNP) from the year 2008 through cash or money incentives. The majority of the conservations were practiced on communal lands. The reason for investing on communal lands was that there was little or no care for conserving and managing communal lands by the individuals. Therefore, the objective of this research was carried out to analysis the roles of Productive Safety Net Program (PSNP) on the practices of soil and water conservation in the case of Sekela District, Amhara State, Ethiopia. Household questionnaire, focus group discussion, case study and Key informants interview methods were applied to collect the necessary information from farm households. A total of 90 households were selected in both served and not served by the program. The survey result shows that in the study area in addition to efforts made by the government soil and water conservation techniques were implemented by the PSN program. But now, the soil conservation techniques practiced by the program was discontinued today. Therefore, before starting to practice of any conservation activity, awareness creation to the people in relation to the use of the technology; and investigate the socio-economic and biophysical variables is very essential.